Tantangan dan Peran Pemerintah dalam Pelaksanaan Landreform di Indonesia - Bakri; Qatrunnada, Aliefia; Herdawati; Syarifudin, Muhammad; Adnan, Indra Muchlis; Syaputra, Didi (Indra Institute Research & Publication, 2023)
Land reform in Indonesia has its ups and downs and in its implementation there are also challenges even though the LoGA has been passed so that the land reform program cannot run smoothly and without obstacles so that this land reform can no longer be carried out in an open and joint way but through a process that is done little by little . In the process of making this journal, the author uses the library research method, which concludes from this journal that the challenges faced in the implementation of land reform include (1) economic and political conditions that are not well established and qualified, (2) strong awareness has not grown between groups. elites, (3) narrow and unequal land ownership, (4) lots of land conflicts and (5) destruction of natural resources. In addition, the role of the government in implementing this land reform is (1) carrying out economic development aimed at justice and people's prosperity, (2) resolving all forms of land conflicts so that ownership rights do not overlap, (3) play an active role in the process of improving natural resources that have been damaged, (4) implementing agrarian law reform, (5) providing free land certificates to the community to realize the agrarian reform program, and apart from that the community must also play an active role in the process of implementing land reform by reporting land to the land office so that rights are protected. ownership of the land.